Association of serum 25-hydroxyvitamin D and homocysteine “double-risk” status with executive dysfunction in older adults with hypertension - Tan, Lili; Zhao, Linya; Li, Hongyan; Zhao, Yamin; Chen, Yinyin (Frontiers in Nutrition, 2026)
BackgroundExecutive dysfunction is common in adults with hypertension and undermines self-management. Low 25-hydroxyvitamin D [25(OH)D] and elevated homocysteine may damage the endothelium and white matter, while their non-linear dose–response and joint effects on executive dysfunction are unclear.MethodsWe conducted a single-center, prospective, cross-sectional study of inpatients aged ≥60 years with hypertension (November 2023–July 2024). Exposures were vitamin D deficiency [25(OH)D < 20 ng/mL] and hyperhomocysteinemia (hymocysteine ≥15 μmol/L), combined into a four-level dual-risk variable. Executive function was a composite of four tests. Non-linear associations were estimated with logistic regression using restricted cubic splines. Multiplicative interaction was assessed after adjustment for demographic, clinical, renal, lifestyle, supplementation, and seasonal covariates.ResultsOut of 498 individuals screened, 452 participants were analyzed. Vitamin D deficiency was observed in 49% participants, with hyperhomocysteinemia in 34%, dual-risk in 22%, and executive dysfunction in 38% participants. Non-linear associations were evident for both biomarkers (p_non-linear ≤0.04). Adjusted odds of executive dysfunction were 1.61 (95% CI 1.2–2.2) at 25(OH)D = 15 vs. 30 ng/mL and 1.4 (1.1–2.0) at homocysteine 18 vs. 10 μmol/L. Relative to neither risk, dual-risk had OR 2.1 (1.5–2.9) with multiplicative interaction (p = 0.03) and additive synergy (excess risk due to interaction 0.45, 95% CI 0.06–0.95).ConclusionIn older hypertensive inpatients, lower 25(OH)D and higher homocysteine are non-linearly associated with executive dysfunction, and co-occurrence confers excess risk beyond individual effects. Assessing both biomarkers may enhance risk stratification and guide trials of combined correction.